2019
DOI: 10.4103/jhrs.jhrs_125_17
|View full text |Cite
|
Sign up to set email alerts
|

A study on chromosomal analysis of patients with primary amenorrhea

Abstract: Background: Primary amenorrhea is one of the most common disorders seen as gynecological problems in adolescent girls. It refers to the participants who did not attain menarche by the age of 11–15 years. Chromosome abnormalities contribute as one of the etiological factors in patients with primary amenorrhea. Aims: The aim of this study was to evaluate the frequency of chromosomal abnormalities and to investigate the abnormal karyotypes in patients referred with the sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
(25 reference statements)
0
11
0
Order By: Relevance
“…These abnormalities are caused by endocrine gland disorders such as thyroid or adrenal gland disorders and genetic, psychological, environmental, or structural anomalies. The cytogenetic investigation has shown that the frequency of chromosomal abnormalities varies from 15.9% to 63.3% in primary amenorrhea (3)(4)(5)(6). The high diversity is probably due to various selection criteria in different reports.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These abnormalities are caused by endocrine gland disorders such as thyroid or adrenal gland disorders and genetic, psychological, environmental, or structural anomalies. The cytogenetic investigation has shown that the frequency of chromosomal abnormalities varies from 15.9% to 63.3% in primary amenorrhea (3)(4)(5)(6). The high diversity is probably due to various selection criteria in different reports.…”
Section: Introductionmentioning
confidence: 99%
“…The sex chromosome abnormalities may be numerical or structural, such as cases with abnormal small X chromosomes because of deletion or iso X chromosomes. There are some types of PA because of the mosaicism of the X chromosome such as X/XXX and X/XX ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…The 46,XY sex reversal phenotypes are one of the important causes of primary amenorrhea in females and 5%–6% primary amenorrhea females are with such male karyotype (Pal et al., 2019). The sex reversal females generally present with hypoplsatic uterus, absence of ovaries or streak gonads (Domenice et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Sex chromosomal aberration is the etiological cause of primary amenorrhea in almost 25% of cases. 12,13 When pubertal development was delayed, a full physical examination is needed to consider broad spectrum of differential diagnosis. 1 Cytogenetic investigations have shown a variety of chromosomal abnormalities as a major cause of amenorrhea.…”
Section: Introductionmentioning
confidence: 99%